Cyfrowy kontekst bibliografii regionalnej (PDF 4,82 MB) (Książnica Śląska, 2025)
This article presents a regional bibliography and its workshop inseveral areas of contemporary librarianship. It serves as a source ofinspiration for other library systems, including digital libraries, particularly in the context of full-text search capabilities, thanks to itsability to describe informational components. Bibliographic compilations represent a valuable information resource, carefully selectedin terms of territory, time, and subject matter, and are readily published by online services. Bibliographies can also be integrated intoextensive information systems, as illustrated by the example of theregional information cluster „Ariadna” at the Silesian Library. In theperspective of creating modern library systems, it can potentiallyserve as an information metasystem, as illustrated by the bibliographic service of North Rhine-Westphalia.